Analysis of brand evaluation behavior: programmed informational reinforcement level and point of sale - Kachuba, Daiane; Oliveira-Castro, Jorge M. (Perspectivas em Análise do Comportamento, 2020)
Behavioral Analysis Principles have been applied to interpret and explain consumption-related phenomena through the Behavioral Perspective Model (BPM). The BPM makes it possible to interpret part of the phenomena that marketing calls brand differentiation as programmed informational reinforcement, typically measured by the Mean Knowledge and Quality (MKQ). Considering that one of the important variables of a brand’s context is where it is sold to the final consumer, the main objective of the research was to examine the relationship between brand differentiation and point of sale. The data were collected through a questionnaire, answered by 120 people, which contained brands of women’s fashion stores, with points of sale in three qualitatively different shopping malls in Brasília, frequented by different groups. Results indicated that the same brand signals different levels of informational reinforcement depending on the point of sale, and higher informational malls increase the potential social reinforcements associated with the brands. In addition, the paper demonstrates the usefulness of behavior-analytic theory in examining brand-choice behaviors by using MKQ as a proximal scale to measure informational reinforcements as programmed social contingencies.